The association of matrix metalloproteinase gene polymorphisms and periodontitis: An overview - Dalal H Alotaibi; Abdulaziz Mohammed Altalhi; Zainah Mohammed Sambawa; Pradeep Koppolu; Aljoharah Abdullah Alsinaidi; Preeti Krishnan (Journal of Pharmacy and Bioallied Sciences, 2020)
Periodontitis is a multifactorial inflammatory disease, pathogenic bacteria being the primary etiological agents. The host response and the severity of clinical manifestation are determined by genetic and environmental factors. There is some evidence that the individual response to environmental variations in the immune response in periodontitis is associated with genetic factors. Matrix metalloproteinases (MMPs) are a family of proteolytic enzymes located in the extracellular matrix. Their primary function is the breakdown of connective tissue components. Their role in the oral cavity is very vital. In this literature review, we summarized the contemporary knowledge on the function of MMPs in oral cavity and periodontal disease.